Infrared Thermography in the Architectural Field. (10th November 2013) - Meola, Carosena
Abstract : Infrared thermography is becoming ever more popular in civil engineering/architecture mainly due to its noncontact character which includes two great advantages. On one side, it prevents the object, under inspection, from any alteration and this is worthwhile especially in the presence of precious works of art. On the other side, the personnel operate in a remote manner far away from any hazard and this complies well with safety at work regulations. What is more, it offers the possibility to quickly inspect large surfaces such as the entire facade of a building. This paper would be an overview of the use of infrared thermography in the architectural and civil engineering field. First, some basic testing procedures are described, and then some key examples are presented owing to both laboratory tests and applications in situ spanning from civil habitations to works of art and archaeological sites.